The Early Phases of Ankylosing Spondylitis: Emerging Insights From Clinical and Basic Science - Watad, Abdulla; Bridgewood, Charlie; Russell, Tobias; Marzo-Ortega, Helena; Cuthbert, Richard; McGonagle, Dennis (Frontiers in Immunology, 2018)
In our paper, discuss how the early phases of ankylosing spondylitis (AS) are linked to peri-firbocartilagenous osteitis in the sacroiliac joint and entheseal bone related anchoring sites. This skeletal proclivity is linked to an abnormal immunological response to skeletal biomechanical stress and associated microdamage. A key event in the early stages of AS appears to be the association with subclinical Crohn’s-like colitis with this gut inflammation being pivotal to the osteitis reaction. Whether this osteitis is consequent to non-specific intestinal innate immune activation or adaptive immune responses against specific microbiotal or self-antigens is unknown. Recurrent iritis is an HLA-B27 associated feature that may predate AS and pursues a course independent of joint involvement, and points towards the pivotal role of organ specific immunology over generalised systemic immune responses in disease expression. Human genetics and animal model studies strongly incriminate the IL23/17 axis and TNF-α in disease pathogenesis. Preliminary work shows a strong convergence of innate immune cells including type 3 innate lymphoid-cells (ILC3) and γδ T-cells in skin, gut, entheseal and eye inflammation. Despite the HLA-B27 association, the role of adaptive immunity, especially CD8 T-cells mediated responses remains unproven and alternative theories have been proposed. The emerging non-dependence of axial inflammation on IL-23 but dependence on IL-17A is an unexpected new twist that awaits full explanation. In this mini-review, we discuss the key events in the early stages of human AS from clinical and basic science aspects, which could be crucial for attempted disease prevention studies in at risk subjects.